CIVILIZATION RUSSIA: PROJECT APPROACH IN PATRIOTIC EDUCATION OF YOUTH - Dmitry N. Bezgodov (Moscow Polytechnic University, 2016)
The article reveals the contents of educational, Kulturtrager project «Civilization Russia». This project was triggered by Ukhta State Technical University in Aug. 2014. The goal of the project is promotion of cultural and civilization achievements of Russia among Ukhta citizens and development of their patriotism. The project includes five components: theoretical foundations, patriotic analytics, civilization achievements of Russia, social and psychological diagnostics, technologies for social communication.